The mosque and the modern world : architects, patrons and designs since the 1950s - Holod, Renata; Khan, Hasan-Uddin.; Mims, Kimberly (London : Thames and Hudson, 1997)
Overzicht in woord en beeld van een aantal moderne moskeegebouwen van over de gehele wereld.
Personal patronage; the state as client; commissions by local government bodies; mosques for public and commercial institutions; local community projects worldwide; Islamic centres in the West.
Includes bibliographical references (pages 280-284) and index.
Keywords: Mosques; Architecture, Islamic